2014
DOI: 10.1088/0953-8984/26/24/244102
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface polarity on water dynamics at the water/rutile TiO2(110) interface

Abstract: We report molecular dynamics (MD) simulations of the water/clean rutile TiO2 (110) interface using polarizable and non-surface polarity force field models. The effect of surface polarity on the water dynamics near the TiO2(110) surface is addressed, specifically by calculating the water hydrogen bond and reorientational dynamics. The hydrogen bond lifetime of interfacial water molecules is several times longer than that of bulk water due to the strong water-TiO2 interactions. A comparison of the dynamics simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 53 publications
4
24
0
Order By: Relevance
“…The atomic positions and Ti−O and O−O bond lengths indicate that; on the hydrophobic surface, the five-coordinated Ti atom was terminated with an O atom [denoted as OT in Figure 5(a)] which is likely in a form of water, the bridging O atom (OB) were not hydroxylated, and the surface was partially covered with adsorbed water molecules (AW) located at a lattice site (the site occupancy was ~0.3). These features are consistent with the previous CTR study on the surface immersed in water [45] and first-principles calculations [42,46]. On the superhydrophilic surface, large positional fluctuations were found for OT, OB, and the topmost TiO layer, and the ordered AW layer was lifted.…”
Section: Monitoring Interface Phe-nomenasupporting
confidence: 91%
“…The atomic positions and Ti−O and O−O bond lengths indicate that; on the hydrophobic surface, the five-coordinated Ti atom was terminated with an O atom [denoted as OT in Figure 5(a)] which is likely in a form of water, the bridging O atom (OB) were not hydroxylated, and the surface was partially covered with adsorbed water molecules (AW) located at a lattice site (the site occupancy was ~0.3). These features are consistent with the previous CTR study on the surface immersed in water [45] and first-principles calculations [42,46]. On the superhydrophilic surface, large positional fluctuations were found for OT, OB, and the topmost TiO layer, and the ordered AW layer was lifted.…”
Section: Monitoring Interface Phe-nomenasupporting
confidence: 91%
“…[21,22] Similarr esults have been experimentally obtained by scan diffuse-reflectance infrared Fourier transform spectroscopy (DRIFTS). This mechanism is in accord with other relevant reports.…”
Section: Influence On the Dynamics Of The Photogenerated Chargessupporting
confidence: 63%
“…This mechanism is in accord with other relevant reports. [21,22] Similarr esults have been experimentally obtained by scan diffuse-reflectance infrared Fourier transform spectroscopy (DRIFTS). It has been found that hydrogen bondingw ith adsorbed water ontoa natase TiO 2 (1 01)s tabilizes surfacetrapped holes, lowers the barrier for hole migration (which enhances carrier mobility), and suppresses chargesrecombination on the timescale of minutes.…”
Section: Influence On the Dynamics Of The Photogenerated Chargessupporting
confidence: 63%
“…This will help us to examine the quality of the spectroscopic models used in our simulations, as well as the lipid and water force fields. As we utilize simple, non-polarizable force fields in this study, we anticipate that better agreement between theory and experiment might be possible with more advanced force fields that take into account explicit polarization effects 74,75 or three-body forces. 76 Agreement between future experiments and our simulations will hopefully allow a detailed insight into and interpretation of interfacial water dynamics at lipid monolayer interfaces.…”
Section: Discussionmentioning
confidence: 99%